The experimental study of the specific pharmacological action of «Artproment» combined gel - О. S. Shpychak; O. I. Tikhonov (Zaporožskij Medicinskij Žurnal)
The preclinical experimental research concerning the study of the specific pharmacological action of "ArtpromentÒ" gel has been done. The gel developed contains propolis phenolic hydrophobic drug, articaine hydrochloride, menthol and rosemary oil in its composition. The medicine is planned to application in sports medicine with the purpose of treating traumatic injuries of organs of the locomotor apparatus accompanied with sport traumas (bruises, dislocations, sprains, ruptures of ligaments, tendons, etc.).